Oral cancer diagnosis amid COVID-19 pandemic: Identifying tell-tale signs to avoid pitfalls in general dental practice. Issue 1 (March 2022) - Jajeh, Neda; Liew, Jonathan; Sainuddin, Sajid; Petersen, Helen
This article details the unusual presentation of an oral squamous cell carcinoma (SCC) referred to secondary care during the COVID-19 pandemic. The patient's chief complaints were trismus and pain from a lower left partially erupted third molar, which was assumed to be pericoronitis-related on referral. Intra-oral examination was difficult due to the patient's symptoms, but radiographic assessment of an orthopantomogram (OPG) showed a pathological fracture and poorly defined radiolucency in the lower left third molar region. Oral SCC was diagnosed after biopsy, and surgery and radiotherapy were swiftly carried out despite COVID-19 restrictions. General dental practitioners (GDPs) remain the frontline healthcare professionals in the screening and detection of oral cancer through detailed history taking and examinations. Primary care dental practitioners should always remain vigilant with patients at risk of oral cancer. Prompt referral to secondary care for further investigations and management should be made when a suspicion of oral malignancy is raised, to ensure a better treatment outcome. Video consultations have had their merits in dentistry amid the coronavirus pandemic, but face-to-face consultations are essential to establish quality patient care.